Band Broadening Function in Size Exclusion Chromatography of Polymers: Review of Some Recent Developments - Meira, Gregorio Raul (2007)
This article reviews some recent developments on the determination of the Band Broadening Function (BBF) in Size Exclusion Chromatography (SEC) of polymers. It was carried out in the frame of the IUPAC Project: "Data Treatment in Size Exclusion Chromatography of Polymers". The correction for band broadening (BB) is important for quantitative determinations of the molar mass distribution (MMD) of narrow-distributed (or highly multimodal) polymers, and of derived variables such as kinetic parameters. In the narrow range of a molar mass standard, the BBF is uniform and of positive skewness. In a broad chromatographic range, the BBF is non-uniform and skewed; and it can be adequately represented by an exponentially-modified Gaussian function (EMG) of 2 parameters that vary slightly with elution volume: an increasing Gaussian variance and a decreasing exponential decay. Additionally, the total BBF variance remains almost constant if not close to the total exclusion limit. The following methods for determining BBF parameters are reviewed: a) a direct method based on assuming Poisson-distributed MMDs; b) a direct method based on measuring the mass- and molar mass chromatograms of narrow standards; c) a theoretical method based on a stochastic model that is equivalent to the Giddings-Eyring model; and d) a theoretical method based on a deterministic model obtained through an extension of the classical van Deemter expression. Ideally, the correction for BB requires a robust numerical inversion algorithm. However, alternative simplified solutions are also possible.